2022
DOI: 10.3390/jcm11030707
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Level in Patients with Consecutive Acute Coronary Syndrome Is Not Correlated with the Parameters of Platelet Activity

Abstract: Coronary artery disease continues to be the leading cause of death in developed countries. Elevated mean platelet volume (MPV) is associated with an increased incidence of myocardial infarction (MI) and MI-related mortality. Vitamin D concentrations affect the level and function of platelets, which are the crucial mediator of atherothrombosis and plaque rupture. The main aim of this study was to examine the relationship of serum 25-hydroxyvitamin D (25(OH)D) levels with the platelet activity in patients with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…Statistically significant disproportions between the subgroups of patients were noticed in terms of sex, diabetes, hyperlipidemia, and smoking. Details on factors influencing the cause of hospitalization were presented elsewhere [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Statistically significant disproportions between the subgroups of patients were noticed in terms of sex, diabetes, hyperlipidemia, and smoking. Details on factors influencing the cause of hospitalization were presented elsewhere [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…This study analyzed NLR and serum vitamin D concentration in a group of patients with a history of MI as part of a research project aiming to describe the relationship between vitamin D level and CAD severity. In previous studies, we showed significantly decreased serum vitamin D concentration in patients hospitalized for ACS compared to those diagnosed with stable CAD [ 38 ] and no significant differences in platelet activity between these two groups of patients [ 37 ]. Vitamin D concentration did not correlate with MPV and P-LCR [ 37 ].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations